2012
DOI: 10.1016/j.micres.2012.02.009
|View full text |Cite
|
Sign up to set email alerts
|

StRas2 regulates morphogenesis, conidiation and appressorium development in Setosphaeria turcica

Abstract: The proteins of Ras family are a large group of monomeric GTPases and act as molecular switches transducing extracellular signals into the cell in higher eukaryotes. However, little is known about roles of Ras family in the foliar pathogens. In this research, we cloned the gene named StRas2 encoding Ras in Setosphaeria turcica and investigated its function by RNA interference technology. We found that the growth rate of RNAi transformants named as R1, R2, R3, R4, R5 and R6, in which the StRas2 silencing effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…For DNA or RNA isolation, fungi were statically cultured in potato dextrose (PD) medium at 25°C. For protoplast preparation, conidia from the cultivated strain 01-23 were cultured in Fries medium for 24 h with shaking (Zhang et al, 2012).…”
Section: Fungal Strains Culture and Transformation Conditionsmentioning
confidence: 99%
“…For DNA or RNA isolation, fungi were statically cultured in potato dextrose (PD) medium at 25°C. For protoplast preparation, conidia from the cultivated strain 01-23 were cultured in Fries medium for 24 h with shaking (Zhang et al, 2012).…”
Section: Fungal Strains Culture and Transformation Conditionsmentioning
confidence: 99%
“…Transformants with the greatest amount of StRas2 suppression display a stunted hyphal phenotype, polarity maintenance defects and reduced conidiation (Zhang et al, 2012b). Exogenous cAMP does not abrogate the aberrant hyphal phenotype but does partially resolve the conidiation defect caused by StRas2 suppression.…”
Section: Plant Pathogenic Fungi: Colletotrichum Trifolii Fusariummentioning
confidence: 99%
“…StRas2 suppression is also associated with loss of appressorium development, reduced appressorial turgur pressure, and reduced pathogenicity. Exogenous cAMP again could not remediate the defects in appressorium development (Zhang et al, 2012b). Therefore, StRas2 may signal through the cAMP/PKA pathway for asexual development but controls hyphal morphogenesis and virulence through cAMP-independent mechanisms.…”
Section: Plant Pathogenic Fungi: Colletotrichum Trifolii Fusariummentioning
confidence: 99%
“…In previous work, we demonstrated that appressorium-mediated infection is regulated by the cyclic AMP and mitogen activated protein kinase signalling pathways under suitable conditions in S. turcica, which indicates a positive interaction between environmental signals and appressorium development (Zhang et al, 2012;Shen et al, 2013;Gu et al, 2014). However, phytopathogenic fungi are frequently challenged by environmental genotoxic stresses that cause DNA damage or interfere with DNA replication.…”
mentioning
confidence: 92%
“…NCLB is a serious fungal foliar disease of cultivated maize that causes devastating loss of yield and a reduction in feed value (Van Inghelandt et al , ). S. turcica develops a specialized cell, called an appressorium, to infect leaves during the pathogen infection cycle (Zhang et al , ; Gu et al , ). S. turcica has emerged as a significant global maize foliar pathogen and causal agent of NCLB, but the regulation of appressorium‐mediated infection remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%